2007
DOI: 10.1042/cs20070018
|View full text |Cite
|
Sign up to set email alerts
|

The dopaminergic system in hypertension

Abstract: Dopamine plays an important role in the pathogenesis of hypertension by regulating epithelial sodium transport, vascular smooth muscle contractility and production of reactive oxygen species and by interacting with the renin-angiotensin and sympathetic nervous systems. Dopamine receptors are classified into D(1)-like (D(1) and D(5)) and D(2)-like (D(2), D(3) and D(4)) subtypes based on their structure and pharmacology. Each of the dopamine receptor subtypes participates in the regulation of blood pressure by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
104
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 171 publications
(378 reference statements)
5
104
0
1
Order By: Relevance
“…At low concentrations, dopamine activates D1 and D2 receptors and dilates interlobular arteries and both the afferent and efferent arterioles, resulting in an increased renal blood flow and a marked natriuretic response. At high concentrations, however, dopamine induces renal vasoconstriction via activation of the ␣-adrenergic receptors (22,29). We previously demonstrated that dopamine is a preferred physiological substrate of PMAT (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At low concentrations, dopamine activates D1 and D2 receptors and dilates interlobular arteries and both the afferent and efferent arterioles, resulting in an increased renal blood flow and a marked natriuretic response. At high concentrations, however, dopamine induces renal vasoconstriction via activation of the ␣-adrenergic receptors (22,29). We previously demonstrated that dopamine is a preferred physiological substrate of PMAT (5).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is synthesized in the proximal tubule and is released as a paracrine and autocrine hormone to act on different receptors in the renal tubules, glomeruli, and renal blood vessels (2,29). Dopamine exerts profound effects on renal hemodynamics in a dosedependant manner (22,29). At low concentrations, dopamine activates D1 and D2 receptors and dilates interlobular arteries and both the afferent and efferent arterioles, resulting in an increased renal blood flow and a marked natriuretic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DA has been shown to regulate behavior, movement, and cardiovascular, renal, endocrine, gastrointestinal, and immune functions (8)(9)(10). Normal blood vessels are supplied by sympathetic nerves, and neurotransmitters released from these nerve endings regulate many critical vascular functions (8,(11)(12)(13)(14)(15). Because DA is one of the catecholamine neurotransmitters in the sympathetic nerve endings and regulates important vascular functions such as vessel tone and blood pressure by acting through its receptors present in blood vessels (8,9,(13)(14)(15)(16)(17)(18)(19)(20), we investigated whether DA has other effects on abnormal tumor blood vessels.…”
mentioning
confidence: 99%
“…behavioural syndromes, sedative effects) or peripheral, some of which affect the cardiovascular system [2]. Cardiovascular effects of DAs are thought to be related to the activation of dopaminergic and non-dopaminergic receptors [17,18]. D1-like and D2-like dopamine receptors located at various sites within the vascular, cardiac and renal regions have been shown to mediate cardiovascular and renal effects [19].…”
Section: Discussionmentioning
confidence: 99%